Kajian Implikasi Undang-undang Cipta Kerja Terhadap Peraturan Daerah Tentang Bangunan Gedung di Kabupaten Wonogiri - Nurokhman, Nurokhman; Wibowo, Richo Andi; Saputra, Ashar; Hariyanto, Gatot (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This research aims to identify the readiness of the Wonogiri Regency in 2021 regarding regional policies in building planning that support the Job Creation Law (No. 11/2020). Several analytical approaches are used with data taken directly through interviews and focus group discussions and other supporting data. As a result, Wonogiri Regency has two options, namely first, the Wonogiri Regency Building Regulations are revoked in their entirety on the grounds that the